2019
DOI: 10.1002/adsc.201901172
|View full text |Cite
|
Sign up to set email alerts
|

Iron Catalyzed Synthesis of Pyrimidines Under Air

Abstract: Herein we report an iron-catalyzed multicomponent dehydrogenative functionalization of alcohols to pyrimidines under atmospheric conditions. Using a well-defined Fe(II)-complex featuring redox noninnocent 2-phenylazo-(1,10-phenanthroline) ligand, as a catalyst, a wide array of 2,4,6-trisubstituted pyrimidines were prepared via dehydrogenative coupling of primary and secondary alcohols with amidines under air at 100°C. A few control experiments were carried out to understand and unveil the plausible reaction me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…Paul and co‐workers established an iron catalysed one‐pot synthesis of 2,4,6‐trisubstituted pyrimidines. [ 79 ] The dehydrogenative coupling reaction between primary 138 and secondary alcohols 137 with amidines 139 generated 2,4,6‐trisubstituted pyrimidines 140 (Scheme 53). The optimised condition for this reaction includes 0.5 equiv.…”
Section: Classificationmentioning
confidence: 99%
“…Paul and co‐workers established an iron catalysed one‐pot synthesis of 2,4,6‐trisubstituted pyrimidines. [ 79 ] The dehydrogenative coupling reaction between primary 138 and secondary alcohols 137 with amidines 139 generated 2,4,6‐trisubstituted pyrimidines 140 (Scheme 53). The optimised condition for this reaction includes 0.5 equiv.…”
Section: Classificationmentioning
confidence: 99%
“…The air-stable iron complex Fe-3 promoted the multicomponent dehydrogenative functionalization of alcohols to form 2,4,6-trisubstituted pyrimidines (Scheme 28c). [47] The iron(II)-complex, featuring a redox noninnocent 2-phenylazo-(1,10-phenanthroline) ligand enabled the synthesis at moderate reaction temperatures with a substoichiometric amount of base in air. The metal-ligand cooperative mechanism was proposed to feature an azo-anion radical iron(II) species as the active catalyst for the one-electron hydrogen atom transfer process to form a ketyl radical intermediate.…”
Section: Pyrimidinesmentioning
confidence: 99%
“…The metal-ligand cooperative mechanism was proposed to feature an azo-anion radical iron(II) species as the active catalyst for the one-electron hydrogen atom transfer process to form a ketyl radical intermediate. [47] Recently a comparative study of nickel-catalyzed dehydrogenative formation of pyrimidines was reported (Scheme 28d). [48] The two catalyst systems are operating in two different pathways.…”
Section: Pyrimidinesmentioning
confidence: 99%
“…Very recently , Paul and co‐workers [91] have introduced redox‐active iron(II) complex ( Fe‐4 , 3 mol%) for the synthesis of pyrimidines ( 98 ) via coupling of guanidine ( 97 ), primary alcohols ( 1 a ) and secondary alcohols ( 1 ) in the presence of relatively low base loading (KO t Bu 0.5 equiv.) and at 100 °C (Scheme 44).…”
Section: Synthesis Of Aromatic Heterocycles Via Catalytic De(hydrogenation)mentioning
confidence: 99%